DNA-enabled fluorescent-based nanosensors monitoring tumor-related RNA toward advanced cancer diagnosis: A review - Dong, Fengqi; Yan, Weizhen; Dong, Wuqi; Shang, Xiaofei; Xu, Yanli; Liu, Wei; Wu, Yunkai; Wei, Wenmei; Zhao, Tingting (Frontiers in Bioengineering and Biotechnology, 2022)
As a burgeoning non-invasive indicator for reproducible cancer diagnosis, tumor-related biomarkers have a wide range of applications in early cancer screening, efficacy monitoring, and prognosis predicting. Accurate and efficient biomarker determination, therefore, is of great importance to prevent cancer progression at an early stage, thus reducing the disease burden on the entire population, and facilitating advanced therapies for cancer. During the last few years, various DNA structure-based fluorescent probes have established a versatile platform for biological measurements, due to their inherent biocompatibility, excellent capacity to recognize nucleic and non-nucleic acid targets, obvious accessibility to synthesis as well as chemical modification, and the ease of interfacing with signal amplification protocols. After decades of research, DNA fluorescent probe technology for detecting tumor-related mRNAs has gradually grown to maturity, especially the advent of fluorescent nanoprobes has taken the process to a new level. Here, a systematic introduction to recent trends and advances focusing on various nanomaterials-related DNA fluorescent probes and the physicochemical properties of various involved nanomaterials (such as AuNP, GO, MnO2, SiO2, AuNR, etc.) are also presented in detail. Further, the strengths and weaknesses of existing probes were described and their progress in the detection of tumor-related mRNAs was illustrated. Also, the salient challenges were discussed later, with a few potential solutions.